Gender differences in the subjective wellbeing of the older adults and the determinant factors: a case study of Nanjing - Feng, Jianxi; Zheng, Min (Frontiers in Public Health, 2024)
Improving the subjective well-being of the elderly is of great significance for achieving 'Healthy Aging'. Nonetheless, quite few studies have been conducted on gender differences in the subjective well-being of the elderly. Based on a survey regarding the quality of life of the elderly in Nanjing in 2021, this paper employs a hierarchical linear model to analyze the gender differences in the impacts of the built environment and household structure on the subjective well-being of the elderly.Results show that there are significant gender differences in the subjective well-being of the elderly, with older women reporting higher levels of subjective well-being.Gender differences also exist in how the built environment and household structure affect the subjective well-being of the elderly. Three mechanisms through which gender affects the subjective well-being of the elderly are proposed, including structural mechanisms, socio-cultural mechanisms and physiological mechanisms. These findings can provide references for targeted environmental interventions and urban planning policies that promote the mental health of the elderly.